Clinical Description, Bacterial Causes and the Association of HIV with Pyodermas Presenting at a Skin Clinic of a Tertiary Hospital in Rural South Western Uganda - Edward, Ogwang; Bazira, Joel; Grace, Mulyowa (International Journal of TROPICAL DISEASE & Health, 2015)
Background: Diagnosis of pyoderma is clinical and antibiotic therapy in low resource setting is largely empirical. At MRRH Skin clinic repetitive visits by some patients with pyoderma led to speculation of antibiotic resistance. This indicated a need to survey the bacterial aetiology of pyoderma, their antibiotic susceptibility, clinical presentation, and look for association with HIV if any. Methods: We consecutively enrolled 216 study participants with clinical diagnosis of pyodermas in a descriptive cross sectional study. Consenting participants had photographic documentation of pyoderma lesions, HIV counselling and testing. Skin swabs were cultured and sensitivity performed on the isolates. Pearson’s chi-square and Fischer’s exact test were performed to determine association between HIV status and bacterial causes of pyoderma Results: Non-bullous impetigo was the commonest clinical presentation, followed by folliculitis/perifolliculitis and lastly ecthyma. The major aetiological agents for the pyodermas were Staphylococcus aureus 77.78% and Streptococcus pyogenes 7.41% respectively. Other bacteria isolated were Klebsiella species 2.31% (5/216), Proteus species 1.85% (4/216) and Pseudomonas species 0.93% (2/216). Resistance of Staphylococcus aureus isolates to the anti-staphylococcal penicillin oxacillin was at 19.53% (33/169). The bacteria isolated from HIV positive participants were no different from that of HIV negative participants; for Staphylococcus aureus (82.35% versus 77.47% or p-value =0.527), Streptococcus pyogenes (5.88% versus 9.34% or p-value = 0.513) and for Klebsiella species (2.94% versus 2.75% or p-value = 0.647). Antibiotic susceptibility to most antibiotics was not significantly different between HIV positive and HIV negative participants except susceptibility to the cephalosporin cefalexin (p-value 0.039) which was much lower in the HIV positive pyoderma patients (83.87% versus 95.12%). Conclusion: Non-bullous impetigo is the most common pyoderma in this population with Staphylococcus aureus and Streptococcus pyogenes being the major causes of pyoderma and pyoderma aetiology was not affected by HIV status
Keywords: Pyoderma; HIV/AIDS; Bacteria; Uganda; Staphylococcus aureus; Streptococcus pyogenes